2012
DOI: 10.3920/cep12009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastric ulcers and relationship to other parameters in Standardbred racehorses

Abstract: Gastric ulcer prevalence rate is reported to be 60-90% in racehorses. This study examined a population of 40 Standardbred horses in race training and assessed the relationship of ulcers to performance history and body condition score (BCS). Forty Standardbreds on two racing facilities in southern Michigan were examined during the last 2 weeks of December 2007 and the second week of January 2008. Age of horses (as of January 1) ranged from 3 to 12 years. Squamous epithelial ulcers were graded (0-4) using an est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…It has recently been suggested that the above prevalences may overstate the prevalence of clinically significant disease as many animals classified as having EGUS may only have mild lesions of questionable clinical relevance (Cate et al . ). The authors generally consider grades 1–2/4 lesions unlikely to cause clinical signs in contrast to grades 3–4/4 lesions, although strong evidence to support this opinion is lacking.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 97%
“…It has recently been suggested that the above prevalences may overstate the prevalence of clinically significant disease as many animals classified as having EGUS may only have mild lesions of questionable clinical relevance (Cate et al . ). The authors generally consider grades 1–2/4 lesions unlikely to cause clinical signs in contrast to grades 3–4/4 lesions, although strong evidence to support this opinion is lacking.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 97%
“…It has also been suggested that the prevalence of ESGD may be overstated in some populations, as many studies include horses with mild (≤ grade 2/4) lesions that may be of questionable clinical significance. 35 Table 1 summarises prevalence data and reported risk factors for ESGD in adult horses and foals.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…; Cate et al . ; Sykes et al . ) as well as in leisure horses, breeding mares and young horses (Le Jeune et al .…”
Section: Introductionmentioning
confidence: 99%